2019
DOI: 10.22161/ijeab.46.25
|View full text |Cite
|
Sign up to set email alerts
|

Access to Agricultural Information among Rural Farmers –A Case of Ido Local Government Area Ibadan, Oyo State, Nigeria

Abstract: The study examined the level of access to agricultural technology information among rural farmers in Ido Local Government, Ibadan, Nigeria. Primary data were collected with the aid of pre-tested questionnaires and 100 respondents were selected through a two stage sampling procedure. The data was analyzed using descriptive statistics and chi-square was used to test the hypothesis.The result of the analyses indicated that (29.1%) falls within the active age bracket of 40-60years, more than half (61.6%) had no fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…This implies the negativity of the result also affirmed that lack of basic infrastructures/storage facilities of farm produce by agricultural cooperative societies. The study agreed with the work of Akanni, Olumide-Ojo, Oyetoki, Asunlegan, Salako, and Jatto, [17] result showed that, source of credit, amount borrowed, and usage of loan obtained have positive impact on agricultural production, while constraints encountered by farmers have negative impact on agricultural production. Few of the respondents sourced for loans from commercial banks, Majority of the respondent used the loan obtained for farming.…”
Section: Socio-economic Factors and Participation Of Rural Dwellers I...supporting
confidence: 89%
See 1 more Smart Citation
“…This implies the negativity of the result also affirmed that lack of basic infrastructures/storage facilities of farm produce by agricultural cooperative societies. The study agreed with the work of Akanni, Olumide-Ojo, Oyetoki, Asunlegan, Salako, and Jatto, [17] result showed that, source of credit, amount borrowed, and usage of loan obtained have positive impact on agricultural production, while constraints encountered by farmers have negative impact on agricultural production. Few of the respondents sourced for loans from commercial banks, Majority of the respondent used the loan obtained for farming.…”
Section: Socio-economic Factors and Participation Of Rural Dwellers I...supporting
confidence: 89%
“…Cooperatives are structured by members in such a way that individuals contribute funds into a joint account with the aim of raising investment, finance and distribute same as easy loans to members. The primary purpose is to encourage savings among members and also offer credit facilities to members to enable them engage in economic activities [17]. Kumar et al [18] believes that the strength of Cooperatives is opined to be advantageous in curbing the problems of poverty alleviation, food security and employment generation as it I seen to have enormous prospective to deliver goods and services in areas where both the public and private sector have failed.…”
Section: Cooperative Conceptmentioning
confidence: 99%
“…Also, the growth of agribusi ness yielded from the higher gross of farm output after a successful selection of the farm input or factors of farm production [25]. Furthermore, factors of production which include; capital while farm special amenities such as modern storage facilities, extension workers, tractors, planters, and water pumping machines among others (land, labour and entrepreneur) are the key sources of the agribusiness and farmer's income through the provision of food security, employment generation, market, and industries as well as a major channel of poverty reduction [26][27][28].…”
Section: Methods Of Researchmentioning
confidence: 99%